New Insights into Behçet's Syndrome Metabolic Reprogramming: Citrate Pathway Dysregulation - Anna Santarsiero; Pietro Leccese; Paolo Convertini; Angela Padula; Paolo Abriola; Salvatore D'Angelo; Faustino Bisaccia; Vittoria Infantino (Hindawi Limited, 2018)
To date, a major research effort on Behçet's syndrome (BS) has been concentrated on immunological aspects. Little is known about the metabolic reprogramming in BS. Citrate is an intermediary metabolite synthesized in mitochondria, and when transported into the cytosol by the mitochondrial citrate carrier-SLC25A1-encoded protein-it is cleaved into acetyl-CoA and oxaloacetate by ATP citrate lyase (ACLY). In induced macrophages, mitochondrial citrate is necessary for the production of inflammatory mediators. The aim of our study was to evaluate SLC25A1 and ACLY expression levels in BS patients. Following a power analysis undertaken on few random samples, the number of enrolled patients was set. Thirty-nine consecutive BS patients fulfilling ISG criteria, and 21 healthy controls suitable for age and sex were recruited. BS patients were divided into two groups according to the presence (active) or absence (inactive) of clinical manifestations. Real-time PCR experiments were performed on PBMCs to quantify SLC25A1 and ACLY mRNA levels. Data processing through the Kruskal-Wallis test and Dunn's multiple comparison test as post hoc showed higher SLC25A1 and ACLY mRNA levels in BS patients compared to those in healthy controls. Therefore, SLC25A1 and ACLY upregulation suggests that metabolic reprogramming in BS involves the citrate pathway dysregulation.